Cultural sponsorship - Spedding, Philip (Henry Stewart Talks, 2009)
Definition of cash sponsorship, Types of income, Assessing your organization and needs, Researching the marketplace, Preparing proposals, Negotiating the partnership, Building relationships with businesses, Evaluation